Walk 14 DOWN THE CIRCUM-BAIKAL RAILWAY - Lidin, Konstantin; Grigoryeva, Elena; Demkov, Sergey; Chertilov, Alexei; Buinov, Alexei; Vedernikova, Tatyana; Antipin, Lyutsian (project baikal, 2014)
Walk 14 DOWN THE CIRCUM-BAIKAL RAILWAYSketch Redesign of the Sverdlovsky Market in Irkutsk "Glazkovo Shopping Arcade"Church of Sts. Apostles Peter and Pavel in Irkutsk – a Rare Monument of Architecture in PribaikalieRedesign of the Church of Sts. Peter and Pavel in IrkutskSt. Nicholas and St. Innokenty Temple in IrkutskRedesign of St. Nicholas and St. Innokenty ChurchRailway Station BuildingProjects of the Railway Station and the Hotel Facilities